(untitled) (International journal of artificial intelligence, 2026)
The article examines the issues of designing an educational electronic resource intended for studying the novel The Master and Margarita by M.A. Bulgakov in the school literature curriculum. Special attention is paid to the didactic and methodological principles underlying the structure of the electronic resource, which contribute to the development of students’ critical and creative thinking. The stages of development, structure, and functional capabilities of the resource are described. The role of digital technologies in increasing students’ motivation and improving the effectiveness of literary text analysis is emphasized. Examples of interactive tasks aimed at developing the reading culture of high school students are provided.